Analisis Yuridis Terhadap Pelanggaran Hak Cipta dalam Konteks Digital - Irpan, Muhamad (Jurnal Jejak Hukum Indonesia (JHI), 2024)
This research aims to conduct a juridical analysis of copyright infringement in the digital context. Advances in technology and the internet have made it easier to distribute digital works, but have also increased the risk of copyright infringement. Copyright is an exclusive right given to the creator of a work to protect his work from unauthorized use. In a digital context, copyright infringement includes the duplication, distribution, and modification of a work without the permission of the copyright owner. This research uses normative legal methods with a qualitative approach to analyze forms of copyright infringement and the protection efforts that can be taken. The research results show that digital copyright violations often occur due to a lack of legal awareness and easy access to technology. Copyright protection in a digital context can be achieved through security technologies such as Digital Rights Management (DRM) and increased law enforcement. This study provides recommendations for increasing legal awareness and use of technology to protect digital copyright.